Cyclodextrin glycosyltransferase biosynthesis improvement by recombinant Lactococcus lactis NZ:NSP:CGT: medium formulation and culture condition optimization - Amiri, Azin; Mohamad, Rosfarizan; Abdul Rahim, Raha; Md. Illias, Rosli; Namvar, Farideh; Tan, Joo Shun; Abbasiliasi, Sahar (Taylor & Francis, 2015)
Cyclodextrin glycosyltransferase (CGTase) is a bacterial glycosyltransferase which catalyses the conversion of starch to cyclodextrin. It can be produced industrially through a fermentation process. The optimal design of the fermentation medium and conditions is critical for metabolic production and microbial growth. Optimization of CGTase biosynthesis by recombinant Lactococcus lactis NZ:NSP:CGT was performed using an artificial neural network (ANN) as the main tool in order to improve the CGTase production in the fermentation process. Three parameters, including temperature, carbon source concentration and nitrogen source concentration, were determined as significant factors for improvement of CGTase production by L. lactis NZ:NSP:CGT in the fermentation process. Soluble potato starch and yeast extract were chosen as the best carbon and nitrogen sources for higher production of CGTase by L. lactis NZ:NSP:CGT. The optimum concentration of soluble starch and yeast extract were 3.82% and 5.67% (w/v), respectively, and the optimum temperature was 20 °C. The final CGTase activity under optimized conditions was 22.09 U/mL, which was close enough to the predicted value of 24.17 U/mL. The obtained results are of particular interest, as CGTase is an industrially important enzyme. In this study, its production through batch fermentation was optimized in order to maximize its production. In future studies, more investigations in various modes of fermentation should be conducted in order to increase the CGTase biosynthesis.